Optimization of Privacy Management for Edho Zell Impression Intensity Improvement - Alvin Alexander Prasetya; Rustono Farady Marta; Laurencia Steffanie Mega Wijaya Kurniawati (INJECT (Interdisciplinary Journal of Communication), 2022)
This article explores Edho Zell’s, a celegram’s privacy management in determining how deep his Instagram’s impressions toward his followers. The videos he uploaded on YouTube depicted his past experiences when he wanted to commit suicide. It was assumed that these should have an effect on the formation of the impression Edho Zell built in a certain period of time. This study employed an explanatory research survey method from a quantitative approach, with the criteria of privacy boundary rules from communication privacy management as the basis for independent variables. Based on the results of data collection through the distribution of questionnaires, it was found that videos containing Edho Zell's personal information had an effect on the formation of his self-image by 45%. It is hoped that through the results of this study, everyone who is categorized as an active social media user can understand how to manage privacy boundaries in terms of forming an impression.